ROLE OF MAGNESIUM IN HEADACHE PATHOGENESIS IN CHILDREN AND ADOLESCENTS - E. S. Akarachkova; S. V. Vershinina; O. V. Kotova; I. V. Ryabokon' (Педиатрическая фармакология, 2013)
Article is dedicated to the problem of headache in children. This pathology is being found more frequently in pediatric and children’s neurologic practice. The authors examine headache pathogenesis from the position of magnesium deficiency. Analysis of results of the modern studies on magnesium deficiency and its correction in patients with headache indicates that magnesium metabolism may play an important role both in pathogenesis of different headache types and in its treatment and prevention.